Curiosity and teachers' creativity: a moderating role of workplace culture. (6th April 2022) - Muhammad, Ghulam; Shah, Syed Muhammad Noaman Ahmed; Chandio, Muiz Ahmed; Saleem, Aneeqa
This study examines the moderating role of workplace culture between the dimensions of curiosity and teachers' creativity. Joyous exploration, stress tolerance, deprivation sensitivity, and social curiosity have been used as the dimensions of curiosity. The population of the study included teachers working in schools in Pakistan. The data has been collected by using five points Likert scale from 350 teachers working in schools of the Sindh region and were analysed through Smart PLS software 3.2.8. The results show that curiosity has a link with the creativity of teachers in schools. The results also indicate that teachers' creativity has a direct link with social curiosity, stress tolerance, and joyous exploration whereas deprivation sensitivity has no relationship. The results also support the moderating role of workplace culture between all the dimensions of curiosity (joyous exploration, stress tolerance and social curiosity) and teachers' creativity except deprivation sensitivity. Managerial implications and limitations also discussed.